PENGARUH EDUKASI SELF CARE TERHADAP KADAR GLUKOSA DARAH SEWAKTU DAN KUALITAS TIDUR PADA PENDERITA DIABETES MELITUS TIPE 2 DI POLI DALAM RSUD PATUT PATUH PATJU - Ernawati; Jannah , Rauhil; Istianah , Istianah (Jurnal Keperawatan Widya Gantari Indonesia, 2024)
Diabetes mellitus is a metabolic disease caused by an increase in blood glucose levels above normal values ​​or the body cannot control blood glucose levels (glucose). Blood glucose is the level of glucose in the blood whose concentration is strictly regulated by the body. Glucose flowing in the blood is the main source of energy for body cells. Self-care education is an individual's activities and initiatives carried out by the individual himself to fulfill and maintain a healthy life and sleep quality. The aim of this research is to determine the effect of self-care education on blood glucose levels and sleep quality in people with type 2 diabetes mellitus. Type of research: quasi-experimental with one group pre and post test design. The number of samples in this study were 18 people taken by porposive sampling technique. The results of the Wilcoxon Signed Ranks Test analysis showed that 16 respondents experienced a decrease in blood glucose and 2 respondents experienced an increase and 18 respondents experienced an increase in sleep quality after being given self-care education with a p value of 0.000, which means that self-care education had an effect on reducing blood glucose and improving quality. Sleep. Thus, this research hopes that patients with diabetes mellitus can understand how to carry out self-care education to improve sleep quality and reduce blood glucose.